Analisis Penerapan Media Pembelajaran berbasis E-Lumak pada Mata Kuliah Statistik Pendidikan PG-PAUD UM Kendari - Usman Usman; Arfin Arfin; Roni Amaludin; Nurlina Nurlina; Risnajayanti Risnajayanti (Journal of Education and Teaching (JET), 2022)
The purpose of the study was to analyze the application of e-lumak media in teaching educational statistics to PG-PAUD students. This type of research is descriptive qualitative. The place and time of the research was carried out at the University of Muhammadiyah Kendari for students who programmed the Education Statistics course for the 2020/2021 Academic Year. The subjects in this study were students and lecturers in education statistics courses. Data collection techniques through observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded as follows: (1) e-lumak media is quite good in online learning in educational statistics courses during the covid-19 pandemic. There are three stages in learning through e-lumak media, including the planning stage, implementation stage, and evaluation stage; (2) The advantages of implementing e-lumak media are very complex features. The drawback of e-lubricant media is that the server is less stable.